Pengaruh Senam Hipertensi Terhadap Tekanan Darah Pada Lansia Penderita Hipertensi Di Panti Wredha Dharma Bhakti Wilayah Kerja Kota Surakarta - Widyaningtyas, Uswatun Hasanah, Okti Sri Purwanti, S.Kep., M.Kep., NS.Sp.Kep.M.B (2016)
ABSTRACT The increasing age of a person, the higher the factor that supports hypertension. Number of patients with hypertension in the elderly is still high. Mild exercise such as gymnastics highly recommended to prevent hypertension. Hypertension gymnastics activities provide many benefits to the elderly, especially in improving the blood pressure. This study aimed to investigate the effect of exercise hypertension on blood pressure in elderly hypertensive patients at Dharma Bhakti Elderly Homes Surakarta Working Areas. The sample in this study consisted of 10 elderly for treatment group in Dharma Bhakti Elderly Homes Wonogiri and also 10 elderly for control group in Dharma Bhakti Elderly Homes Pajang Surakarta. Hypertension gymnastics was done for 2 weeks or 6 meetings. Blood pressure measuring tools using spignomanometer and stethoscope. Data were analyzed using T-test test either in pairs or independently. The results of the study in the control group before treatment, mostly with hypertension mild (grade I) and moderate (stage II) and and after treatment, mostly with hypertension mild (grade I) and moderate (stage II). An average of 161/102 mmHg before it dropped to 156/97 mmHg. In the control group before treatment, mostly with mild hypertension (stage I) and moderate (stage II) and and after the treatment is done mostly with mild hypertension (stage I) and hypertension high normal categories. On average before an average of 161/102 mmHg decreased to 136/87 mmHg. The conclusions of the study there is significant differences in blood pressure before and after in treatment group. There is no significant differences in blood pressure before and after treatment in the control group. There was a significant effect of hypertension gymnastics on blood pressure in elderly patients with hypertention in Dharma Bhakti Elderly Homes Surakarta Working Areas. Keywords: Elderly, Hypertension, Gymnastics, Blood Pressure